The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/gutjnl-2019-318264
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF therapy in IBD exerts its therapeutic effect through macrophage IL-10 signalling

Abstract: ObjectiveMacrophage interleukin (IL)-10 signalling plays a critical role in the maintenance of a regulatory phenotype that prevents the development of IBD. We have previously found that anti-tumour necrosis factor (TNF) monoclonal antibodies act through Fcγ-receptor (FcγR) signalling to promote repolarisation of proinflammatory intestinal macrophages to a CD206+ regulatory phenotype. The role of IL-10 in anti-TNF-induced macrophage repolarisation has not been examined.DesignWe used human peripheral blood monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 39 publications
4
90
0
Order By: Relevance
“…The presence of CD206 + regulatory macrophages has been proposed as a favorable prognostic factor in determining the response rate to anti-TNFα therapy in patients with CD (15,16). In addition, recent studies even suggest that induction of CD206 + macrophages vai the Fc 5 portion of ipilimumab mediating the activation of the Fcγ receptor maybe an essential component of the anti-TNFα therapy (40). The correlation between the expression of EP4 and CD206 observed in our study indicates a new mechanistic role of PGE2 in inducing wound healing macrophages.…”
Section: Discussionsupporting
confidence: 64%
“…The presence of CD206 + regulatory macrophages has been proposed as a favorable prognostic factor in determining the response rate to anti-TNFα therapy in patients with CD (15,16). In addition, recent studies even suggest that induction of CD206 + macrophages vai the Fc 5 portion of ipilimumab mediating the activation of the Fcγ receptor maybe an essential component of the anti-TNFα therapy (40). The correlation between the expression of EP4 and CD206 observed in our study indicates a new mechanistic role of PGE2 in inducing wound healing macrophages.…”
Section: Discussionsupporting
confidence: 64%
“…Accordingly, anti-TNF agents are effective in moderate and severe IBD in both children and adolescents, and their application resulted in limiting the use of corticosteroids [54]. A recent study has demonstrated that the therapeutic role of anti-TNF agents is critically dependent on IL-10 to resolve intestinal inflammation [55]. Hence, it is noteworthy assuming that IL-10 plays a role in the ameliorative effect of Aloe and/or HK L.137 on colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, anti-TNF therapy response rests on TNF neutralisation, but specifically in CD also on its potency to bind membrane bound TNF on CD-tissue infiltrated macrophages 38 , which causes differentiation of 11 macrophages to a more regulatory CD206 + M2-like phenotype 31,39 . This is for example evidenced by the clinical observation using etanercept (does not bind membrane bound TNF), which is not effective in CD, whilst infliximab is 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that successful anti-TNF therapy is associated with an increase in CD206 + regulatory macrophages 31 and a decrease in pro-inflammatory cytokines 10 and SP140 expression 10 in CD mucosa. Thus, our data suggests that SP140 inhibition could be also beneficial in supporting the anti-TNF therapy.…”
Section: Gsk761 Reduces the Inflammatory Activation Of Macrophages Anmentioning
confidence: 99%